The incidence of cardiovascular thrombotic complications after laparoscopic resection in colorectal cancer in Japanese hospitals: A large‐scale clinical study. Issue 3 (12th December 2021) - Ichikawa, Nobuki; Homma, Shigenori; Funakoshi, Tohru; Obuchi, Keisuke; Ohshima, Takahiro; Uemura, Kazuhito; Kon, Hirofumi; Ohno, Yosuke; Yokota, Ryoichi; Taketomi, Akinobu; ,
Abstract: Aim: The aim of this retrospective study was to investigate the incidence of cardiovascular thrombotic complications after laparoscopic resection in colorectal cancer. Methods: This study involved 2017 patients with stages 0‐III colorectal cancer who underwent laparoscopic surgery at 17 Japanese hospitals between January 2010 and December 2013. We assessed the incidence of postoperative cardiovascular thrombotic and haemorrhagic complications. Results: Laparoscopic surgeries were performed in 1152 men and 865 women with 1405 colon and 612 rectal cancers, respectively. Overall, 3%, 38%, 17%, 8%, and 9% of patients had comorbidities of heart failure, high blood pressure, diabetes, history of stroke, and vascular disease, respectively. Antithrombotic agents were being consumed by 17% of patients. The types (and perioperative rest periods) of the antithrombotic agents were aspirin in 58% (18.6 days), clopidogrel in 19% (21.1 days), cilostazol in 13% (13.3 days), and warfarin potassium in 21% (14.6 days) of cases with antithrombotic agents. Surgical time and blood loss in the total cohort were 234 minutes and 56 mL. Four cases (0.2%) had cardiovascular thrombotic complications, including one severe cardiac infarction and one stroke with major sequelae (CHADS2 scores were 2 points in both cases). Hemorrhagic complications occurred in 19 cases (0.9%). In particular, the incidence of the major gastroduodenal haemorrhagic ulcer was higher in cases with antithrombotic agents than without them (0.05% vs 0%, P = .02). Conclusion: The incidence of cardiovascular thrombotic complications was rare, although severe cardiac infarction and stroke could occur even after minimally invasive surgery in colorectal cancer. Abstract : We assessed the incidence of postoperative cardiovascular thrombotic complications after laparoscopic colorectal resections for colorectal cancer. Four out of 2017 cases (0.2% with 95% Confidence Interval, 0.08%‐0.5%) had cardiovascular thrombotic complications, including one severe cardiac infarction and one stroke with major sequelae.